Effect of Plasma Treatment (He/CH4) on the Glass Surface for the Reduction of Powder Flux Adhesion in the Spray Drying Process - Ramlan, Nadiah; Mohd Zamri, Nazirah Wahidah; Maskat, Mohamad Yusof; Md Jamil, Mohd Suzeren; Chin, Oi Hoong; Lau, Yen Theng; Zubairi, Saiful Irwan (Penerbit Universiti Kebangsaan Malaysia, 2018)
A 50Hz glow discharge He/CH4 plasma was generated and applied for the glass surface modification to reduce the powder adhesion on wall of spray dryer. The hydrophobicity of the samples determined by the water droplet contact angle and adhesion weight on glass, dependent on the CH4 flow rate and plasma exposure time. The presence of CH3 groups and higher surface roughness of the plasma treated glass were the factors for its hydrophobicity development. Response surface methodology (RSM) results using central composite rotatable design (CCRD) showed that optimal responses were obtained by the combination of parameters, CH4 gas flow rate = 3 sccm and exposure time = 10 min. In optimum conditions, the contact angle increased by 47% and the weight of the adhesion reduced by 38% (w/w). The plasma treatment could enhance the value of the contact angle and thus reduced the adhesion on the spray dryer glass surface.